Perfect Extinction of Terahertz Waves in Monolayer Graphene over 2-nm-Wide Metallic Apertures - Park,H-R; Namgung,S; Chen,X; Lindquist,NC; Giannini,V; Francescato,Y; Maier,SA; Oh,S-H (Advanced Optical Materials, 2015)
High carrier mobility and tunability in graphene enable fundamental studies for plasmonics and various applications. Despite its versatility, however, single-layer graphene (SLG) suffers from poor coupling efficiency to electromagnetic waves, presenting a major challenge for photonic applications. Compared with visible or infrared radiation, terahertz (THz) waves exhibit higher absorption in SLG due to Drude-like intraband transitions, but the wavelength-to-SLG size mismatch becomes even more dramatic. Here, we experimentally demonstrate 99% extinction of THz wave transmission when SLG covers the openings of 2-nm-wide (≈λ/1 000 000) slits through a metal film. By resonantly coupling THz waves through annular nanogaps, the extremely localized fields lead to near-perfect extinction and strong absorption in SLG. Atomic-layer lithography is used to produce these nanometer-wide, millimeter-long gaps over an entire 4-in. wafer. Furthermore, by integrating these devices with an ionic liquid, enhanced intraband absorption in the SLG leads to 80% modulation of THz waves with an operational voltage as low as 1.5 V.